Implikasi Penerapan Polisi Akhlak terhadap Budaya Sekolah di SD Muhammadiyah Kranggan - Dini Afriyani; Mar’atul Faida; Dian Kusumawati (Mataram University, 2026)
This study was conducted to examine the implications of the implementation of the moral police for school culture at SD Muhammadiyah Kranggan. A descriptive qualitative approach was adopted, involving the principal, teachers, student members of the moral police, and non-member students selected through purposive sampling. Data were obtained through observation, semi-structured interviews, and documentation, and analyzed using the Miles and Huberman interactive analysis model. The results show that the moral police strengthens religious values, discipline, politeness, social responsibility, cleanliness and healthy habits, learning culture, honesty, and environmental awareness through continuous habituation and active student participation. Its implementation is supported by the principal, teachers, school regulations, and collaboration among all members of the school community. However, several challenges remain, including unequal student awareness of school rules, limited self-confidence among some student members when reminding their peers, and limited supervision. These findings suggest that the moral police program is an effective strategy for strengthening school culture through consistent habituation. The findings also provide practical implications by serving as a reference for other schools in developing character education programs based on students' active participation to foster a positive and sustainable school culture.